Cholesterol metabolism: a new molecular switch to control inflammation. Issue 11 (11th June 2021) - Cardoso, Diana; Perucha, Esperanza
Abstract: The immune system protects the body against harm by inducing inflammation. During the immune response, cells of the immune system get activated, divided and differentiated in order to eliminate the danger signal. This process relies on the metabolic reprogramming of both catabolic and anabolic pathways not only to produce energy in the form of ATP but also to generate metabolites that exert key functions in controlling the response. Equally important to mounting an appropriate effector response is the process of immune resolution, as uncontrolled inflammation is implicated in the pathogenesis of many human diseases, including allergy, chronic inflammation and cancer. In this review, we aim to introduce the reader to the field of cholesterol immunometabolism and discuss how both metabolites arising from the pathway and cholesterol homeostasis are able to impact innate and adaptive immune cells, staging cholesterol homeostasis at the centre of an adequate immune response. We also review evidence that demonstrates the clear impact that cholesterol metabolism has in both the induction and the resolution of the inflammatory response. Finally, we propose that emerging data in this field not only increase our understanding of immunometabolism but also provide new tools for monitoring and intervening in human diseases, where controlling and/or modifying inflammation is desirable.